2020
DOI: 10.3389/fimmu.2020.00545
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Circular RNAs in Immune-Related Diseases

Abstract: Circular RNAs (circRNAs) are a novel class of RNAs with a covalently closed loop structure without a 3 ′ polyadenylation [poly-(A)] tail or a 5 ′ cap. They used to be considered as the occasional and useless products of RNA splicing errors because they could not be detected by traditional RNA sequencing technology. Benefiting from the development of specific biochemical and computational approaches, researchers showed that circRNAs are universally expressed and functional. Further studies have revealed their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 89 publications
(92 reference statements)
0
31
0
Order By: Relevance
“…CircRNAs, consisting of covalently closed continuous loops, are a newly identified type of ncRNAs with the ability to encode proteins, regulate gene transcription, and act as a special “sponge” for miRNAs and harbor abundant miRNA binding sites [ 44 ]. Unlike the above two linear miRNAs and lncRNAs, due to the 3′ and 5′ ends commonly presented are firmly concatenated, circRNAs exist in multiple species with high abundance, high sequence conservation, and specific expression [ 45 , 46 ]. Aberrant circRNAs expression plays a crucial regulatory role during the occurrence and development of fibrosis diseases, including hepatic fibrosis, cardiac fibrosis, and keloid.…”
Section: Epigenetic Modification Expression Profile In Keloidmentioning
confidence: 99%
“…CircRNAs, consisting of covalently closed continuous loops, are a newly identified type of ncRNAs with the ability to encode proteins, regulate gene transcription, and act as a special “sponge” for miRNAs and harbor abundant miRNA binding sites [ 44 ]. Unlike the above two linear miRNAs and lncRNAs, due to the 3′ and 5′ ends commonly presented are firmly concatenated, circRNAs exist in multiple species with high abundance, high sequence conservation, and specific expression [ 45 , 46 ]. Aberrant circRNAs expression plays a crucial regulatory role during the occurrence and development of fibrosis diseases, including hepatic fibrosis, cardiac fibrosis, and keloid.…”
Section: Epigenetic Modification Expression Profile In Keloidmentioning
confidence: 99%
“…Although studies on the biological functions and mechanisms underlying the effects of circRNAs in autoimmune diseases are finite, a considerable number of studies have revealed their effects on molecular biological processes and immune regulation of various immune cells. 7 , 62 , 63 , 64 For instance, circ-ANRIL induces nucleolar stress and p53 activation, resulting in the apoptosis elevation and proliferation suppression in macrophages. 65 circRNA-002178 can be delivered by exosomes into CD8 T cells to induce PD1 expression, leading to T cell exhaustion.…”
Section: Circrnas and Diseasesmentioning
confidence: 99%
“…Present studies have revealed that miR‐7 can regulate α‐synuclein by directly binding to SNCA gene 3′‐untranslated region; and a decreased level of miR‐7 is seen in substantia nigra of PD patients. As high expression of CDR1‐AS is seen in human and mouse brain and due to its role in miR‐7 sponging, it is believed that this circle RNA may be a good target as a therapeutic target for PD (Junn et al, 2009; Xie, Zhang, Zhang, Li, & Zhou, 2020).…”
Section: Alzheimermentioning
confidence: 99%